Optimalisasi Sumber Daya Lingkungan dan Edukasi Kreatif untuk Pemberdayaan Masyarakat - Aditama, Marangga; Yasmin, Yasmin; Ismirandha, Savina; Saputu P.M , Batara Guru; Algoniyah, Muhammad Demas; Novitasari, Lili; Setyaningtyas, Sekar Ayu; Fadhilal N, Jiddan Ahmad; Shalaila, Syifa; Rianda, Adam Maulana; Sutrisno, Sutrisno (Universitas Muhammadiyah Yogyakarta, 2025)
Program Kuliah Kerja Nyata (KKN) plays a strategic role in improving community welfare through empowerment, one of which is by utilizing livestock waste into organic fertilizer. This program aims to increase public awareness of the economic and ecological potential of livestock waste and provide practical skills in processing it into useful organic fertilizer. The methods used include direct counseling, joint practice, and regular monitoring of the quality of the fertilizer produced. Counseling provides an understanding of the benefits of organic fertilizer for soil fertility and reducing dependence on chemical fertilizers. Joint practice involves KKN students and local residents in the fertilizer making process, from waste collection to fermentation. Regular monitoring is carried out to ensure that the quality of the fertilizer meets standards. The results of this KKN program show a significant increase in community understanding of the benefits of livestock waste as organic fertilizer, as well as increased skills in the manufacturing process, as measured by active participation in training and increasing the quantity of organic fertilizer production at the local level